Stress Levels Among Men and Women with Coronary Heart Disease. Is there a Difference? - Rafika Rosyda; Dimas Yusuf Irawan; Nunung Siti Sukaesih (Universitas Pendidikan Indonesia, 2022)
Coronary Heart Disease (CHD) is one of the non-communicable diseases with a very high mortality rate. CHD can occur in both men and women. CHD is usually followed by psychological reactions such as stress, and stress may contribute to progression of CHD. This study aims to determine the difference between stress levels in men and women with CHD. This research used comparative quantitative methods that used a questionnaire from Kessler Psychological Distress K10. Enrolled 95 samples by random sampling. The results of this study showed that there is no difference in stress levels among men and women with CHD (p=0.083, 0.05). Both men and women with CAD have experienced stress, but there is no significant difference between men and women.